Phytochemical, Chemotaxonomic and Bioinformatics Study on Laportea bulbifera (Urticaceae). Issue 7 (8th June 2022) - Lu, Xuan; Zhao, Yuxuan; Li, Bo; Feng, Weixing; Qi, Junkai; Feng, Baomin
Abstract: Phytochemical investigation of the aerial part of Laportea bulbifera (Siebold & Zucc.) Wedd. ( L. bulbifera ) showed the isolation of seventeen compounds, including five flavonoids (1 –4 and 6 ), one terpenoid (5 ), five phenolic acids (7 –11 ), one coumarin (12 ), two steroids (13 –14 ), and three alkaloids (15 –17 ). Structure elucidations of these compounds were performed on the basis of extensive NMR experiments and compared with the published data in the references. It is remarkable that compounds (3 –5 ) were firstly isolated from the Urticaceae family, compounds (3 –8, 11 and 15 –17 ) were firstly obtained from genus Laportea . Furthermore, the result of the chemotaxonomic significance discussion showed that compounds (2 –4 ) may can be served as compound fingerprints to distinguish between species of L. bulbifera and genus Urtica, and what' more, we proposed a bold conjecture that isoflavones can distinguish between species of L. bulbifera and genus Urtica . At the same time, the molecular docking method was used to evaluate the inhibitory effect of these compounds on human steroid 5α‐reductase 2 (SRD5α2). The results showed that compounds (1 –4 and 6 ) had better expected effects than the positive drug finasteride can by effectively binding to the active sites of SRD5α2. This study assisted in the future phytochemical and chemotaxonomic research on genus Laportea . Simultaneously, this research provided the theoretical evidence for the application of L. bulbifera in treating benign prostatic hyperplasia (BPH). Abstract :